Management of patients receiving novel antithrombotic treatment in endodontic practice: Review and clinical recommendations. (20th August 2021) - Lin, Shaul; Hoffman, Ron; Nabriski, Omri; Moreinos, Daniel; Dummer, Paul M. H.
Abstract: Cardiovascular diseases are a major component of non‐communicable diseases and death, with thrombosis constituting the most common underlying pathosis of the three major cardiovascular disorders: ischaemic heart disease (acute coronary syndrome), stroke and venous thromboembolism (VTE). The introduction of direct oral anticoagulants (DOACs) in recent years has necessitated a more complex approach to periprocedural and perioperative anticoagulation management and the need for revised management strategies and protocols. Currently, patients taking classic oral anticoagulants are advised to stop taking the drugs and have their INR values checked 72 h prior to dental surgery (e.g., apical surgery, tooth extraction, and periodontal surgery) and checked again 24 h prior to the procedure to ensure it is within the therapeutic range. However, the current incorporation of these novel DOACs in routine medical practice requires changes in the way patients are managed preoperatively in dentistry, and specifically in endodontic surgery. The methodology applied in this review included searching for relevant articles in the PubMed database using keywords listed in the Entree Terms databases. Articles published on human blood clotting mechanism, antithrombotic drugs, as well as treatment guidelines and recommendations for dentistry were retrieved. In addition, textbooks and guidelines that may not have surfaced in the online search were searched manually. The aim of this paper was to review the mechanisms of action of classic and novel antithrombotic medications and their impact on endodontic treatment and the management of local haemostasis in endodontics.